Molly Bjustrom: capstone - Bjustrom, Molly, artist (Colorado State University. Libraries, 2015)
The artist's statement: The Eleventh Hour Final: Installation. Flashforbe Pro 3D Printer and Makerbot 3D Printer displayed in found 1960's television sets, PLA and ABS plastic crystals, mirrored acrylic, LED lights, filing drawers; chakra wall hangings, crocheted blanket-covered floor pillows, coffee table; found objects include: layered rugs, floor lamp, curtains, crystal reference books, 9' x 10' x 12'. This living room installation was inspired by Edward Kienholz, a 1960's Funk and Socio-political artist, thus the title of this work specifically addresses his 1968 installation. I wanted to evoke the comforting atmosphere of an average living room from the late 60's. And like Kienholz, I then wanted to break that atmosphere with the focus shifted to one object: the running 3D Printer installed in a 1960's television. Unlike Kienholz, the question I ask is much lighter in context than the Vietnam War. I ask: What can technology that seems so remote and far away mean to most people in the familiar setting of their middle class homes? Jellyfish Installation No. 2: Installation. Molded plastics, EL wire, LED, fiber optics, blue flood lights, aluminum wire mesh, wire, tulle, yarn, felt, ribbon, various textiles, beads and found objects (includes plastic bottles, scarves, doilies, skirts, lace veils, crocheted pieces, and sewing materials, fishing tackle). 12' x 14' x 19'. "Some ancient healers who hold the belief that the tapestry of true spiritual knowledge is held within the transparent form of the jellyfish". - Ina Woolcott. Jellyfish symbolize acceptance and faith; they embrace and trust that All That Is will provide the necessities for them to thrive. They trust that the oceans' currents and that the strong winds will urge them on The Path that they must go-they possess almost no ability to travel on their own. Jellyfish are blessed with the virtue of floating in harmony with life's path rather than trudging through life's currents. Meditate on your life-are you flowing with life in a balanced manner or are you squandering, drifting aimlessly and overlooking Dharma-to dynamically cross the currents toward your Karma. Look within yourself and contemplate the jellyfish, through this balance can be realized.
The eleventh hour final
Jellyfish installation no. 2
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.